The Effect of Academic Supervision on Learning Quality: A Quantitative Study in Driving Primary Schools in Rembang Regency - Imamuddin Sa'id; Ali Shodiqin; Soedjono Soedjono (FKIP - Universitas Riau, 2026)
Improving the quality of learning in primary schools is a key priority in current educational transformation, requiring effective professional support for teachers through academic supervision. This study aims to examine the effect of academic supervision on learning quality in Sekolah Dasar Penggerak (Driving Primary Schools) in Rembang Regency. A quantitative survey design was employed involving 107 teachers as respondents. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability and were analyzed using descriptive statistics, Pearson correlation, and simple linear regression. The results indicate that academic supervision was implemented at a moderately high to high level, while learning quality was also categorized as moderately high. Correlation analysis revealed a positive and significant relationship between academic supervision and learning quality (r = 0.725; p = 0.004). The coefficient of determination showed that academic supervision accounted for 52.6% of the variance in learning quality. These findings suggest that systematic, continuous, and professionally oriented academic supervision plays a crucial role in enhancing the quality of classroom instruction in Driving Primary Schools.